A retrospective study of brochoscopic profile of patients in a tertiary care centre - Kumar, Amit; Choudhary, Prashant; Khan, Javed; Saini, Rishi (International Journal of Research in Medical Sciences, 2018)
Background: The purpose of this study was to find out the demographic profiles, indications, bronchoscopic findings and diagnosis of the patients who underwent bronchoscopic examination. Methods: A retrospective analysis of 200 consecutive fiber-optic bronchoscopies was performed at RMCH from June 2015 to June 2017 to find out the demographic and clinical profile of the patients who underwent this procedure. The instrument Olympus video bronchoscope was used for the procedure. Results: Among total of 200 patients, 131 (65.5%) were males and 69 (34.5%) patients were females. 150 (75%) patients were smokers and 50 (25%) patients were non- smokers. Cough was the most common presenting symptom in 180 (90%) of the patients followed by breathlessness 138 (69%), chest pain 114 (57%), hemoptysis 80 (40%), fever 66 (33%). The most common finding is endobronchial growth in 119 (59.5%) followed by nonspecific inflammation 40 (20%), inconclusive 21 (10.5%), normal 12 (6%), suspected growth 8 (4%).Out of 200 patient biopsy was done in 65 patients (32.5%) and most common histopathological diagnosis was malignancy 42 (64.61%), pulmonary tuberculosis 10 (15.38%), Infective pathology 9 (13.8%), inconclusive 4 (6.1%). Conclusions:Bronchoscopy is a safe and useful tool for making the diagnosis of a variety of pulmonary diseases. Endobronchial growth and malignancy were the commonest findings on bronchoscopy and histopathological examination respectively. Moreover, we would like to emphasize the importance of attempting biopsy from the abnormal segment of the lung even when bronchoscopy does not show frank mucosal growth.